A 1-D gas dynamics code for subsonic and supersonic flows applied to predict EGR levels in a heavy-duty diesel engine. (20th February 2004) - Zhu, Yuhua; Reitz, R.D.
The development of a 1-D gas dynamics code for unsteady flow in internal combustion (IC) engines as well as its validation and application for predicting residual gas fraction are introduced in this paper. Some new approaches are presented for modelling flows in diverging ducts and for treating boundary conditions. These include the use of flow resistance correlation to describe separated flows and flows in bends. Excellent agreement with analytical solutions and test results has been obtained when the code was validated with fundamental gas dynamic problems, including converging-diverging nozzle flows with and without shocks; Fanno and Rayleigh flows; the Riemann shock tube problem; and engine rig experiments for modelling flow with different property gases. The code has been applied satisfactorily to predict the gas exchange process of a spark ignition (SI) engine following exhaust blow-down and exhaust gas recirculation (EGR) levels in a heavy-duty diesel engine.